A New Era of Customary Property Rights?-Liberia's Land and Forest Legislation in Light of the Indigenous Right to Self-Determination - Rösch, Ricarda (Verfassung und Recht in Übersee, 2019)
After the end of Liberia's civil war in 2003, the country embarked upon the reform of its forest and land legislation. This culminated in the adoption of the 2009 Community Rights Law with Respect to Forest Lands and the 2018 Land Rights Act, which NGOs and donors have described as being amongst the most progressive laws in sub-Saharan Africa with regard to the recognition of customary land tenure. Given these actors commitment to human rights, this article takes the indigenous right to self-determination as a starting point for analysing customary property rights and their implementation in Liberia. This includes the examination of the Liberian concept of the 1) recognition and nature of customary land rights, 2) customary ownership of natural resources, 3) jurisdiction over customary land, 4) the prohibition of forcible removal, and 5) the right to free, prior and informed consent.
CRIS-Team Scopus Importer:2024-12-16

Under the Disguise of Participation: Community Forestry as a New Form of Land Rush in Liberia - Rösch, Ricarda (The Transnational Land Rush in Africa, 2021)
A variety of national and international actors embarked upon the reform of the Liberian forest sector after the end of the civil war in 2003, in part due to the logging sanctions enacted by the United Nations during the conflict. One result of these reform efforts was the adoption of the Community Rights Law with Respect to Forest Lands in 2009. The law introduces community forestry and is considered to be one of the most progressive laws on the African continent. Yet, fieldwork in Liberia conducted between October 2017 and January 2018 and between February and March 2018 indicates that the community forestry regime is redefined and undermined by different actors, and, in practice, contributes to land grabbing. After providing a brief overview of the government’s post-war Foreign Direct Investment (FDI) strategy, this chapter explores: (1) the reform of the logging sector after the war (2) the legal framework of community forestry, and (3) the implementation of community forestry based upon two case studies.
CRIS-Team Scopus Importer:2021-02-26
Keywords: Community forestry; Customary land rights